Adult acute lymphocytic leukemia biology and treatment - Advani, Anjali; Lazarus, Hillard M. (Contemporary hematology., 2011)
The current explosion of new areas of controversy in the treatment of acute lymphocytic leukemia in adults and young adults makes this comprehensive book a much needed reference for hematologists and oncologists. This book assembles leading authorities from around the globe to cover the full spectrum of ALL subtypes and their treatments. Specific topics of discussion include indications for allogeneic bone marrow transplant in first complete remission, the role of minimal residual disease in making treatment decisions, the treatment of young adults, and the treatment of Philadelphia chromosome positive ALL with the advent of the tyrosine kinase inhibitors. This is the first book to focus exclusively on the adult ALL patient. It provides a complete overview of diagnosis, molecular pathogenesis, evaluation, and treatment for this important patient population.